2015
DOI: 10.1186/s40608-015-0045-5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of how researchers characterize the school environment in determining its effect on student obesity

Abstract: BackgroundObesity in early childhood is a robust predictor of obesity later in life. Schools provide unparalleled access to children and have subsequently become major intervention sites. However, empirical evidence supporting the effectiveness of school-based interventions against childhood obesity is of limited scope and unknown quality. The aim of this systematic review is to critically assess how researchers have characterized the school environment in determining its effect on childhood weight status in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…A systematic review of school environment changes found a limited evidence base (only UK and US studies), but these showed potential to improve health 11 . Another review found that there was a lack of evidence to show that the school environment determined obesity, but there was also a lack of validated tools to assess the school environment 12 . A review of school policies that limit access to sugary drinks and energy dense foods found mixed, but generally supportive, evidence for these policies in preventing obesity 13 .…”
Section: School Environment and Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of school environment changes found a limited evidence base (only UK and US studies), but these showed potential to improve health 11 . Another review found that there was a lack of evidence to show that the school environment determined obesity, but there was also a lack of validated tools to assess the school environment 12 . A review of school policies that limit access to sugary drinks and energy dense foods found mixed, but generally supportive, evidence for these policies in preventing obesity 13 .…”
Section: School Environment and Healthmentioning
confidence: 99%
“…11 Another review found that there was a lack of evidence to show that the school environment determined obesity, but there was also a lack of validated tools to assess the school environment. 12 A review of school policies that limit access to sugary drinks and energy dense foods found mixed, but generally supportive, evidence for these policies in preventing obesity. 13 For example, sales restriction at school had only limited effect on high school students' overall consumption of sugary drinks in Maine, 14 but was effective in Boston.…”
Section: School Environment and Healthmentioning
confidence: 99%
“…The school setting has been recognized as an important intervention venue for obesity prevention because children and adolescents spend a significant amount of time in schools and share the surrounding environment that might influence their energy balance‐related behaviours, including diet and physical activity . Overall, school‐based obesity prevention programmes have been found to be most effective when they are theory‐based, behaviourally focused, long‐term (1‐4 years), include multicomponents such as parent involvement, and when the school environment and policy modifications are incorporated within the intervention programmes …”
Section: Introductionmentioning
confidence: 99%
“…Possible reasons for the limited success rates on obesity outcomes may vary but might include lack of methodological rigour including small number of schools, short‐term follow‐ups, lack of multicomponent strategies, and inconsistent intervention implementation. In addition, studies can be underpowered if there are high school‐level clustering effects in obesity outcomes that are not taken into account in the study design . Previous studies have shown considerable between‐school variation in obesity outcomes as well as behaviours related to energy balance .…”
Section: Introductionmentioning
confidence: 99%
“…The school built environment can be measured using surveys or objective methods to identify features that influence these behaviors. [10][11][12][13][14][15][16][17] Although surveys of school personnel are arguably easier to employ and are currently included as a component of several studies, 18 they can be burdensome for school staff, which may result in incomplete data, and may be subject to biased and/or incomplete reporting of school amenities. Objective assessments (often termed as 'audits') of the school built environment by study staff, on the other hand, pose little-to-no burden on school personnel and result in complete and verified data for all schools.…”
Section: Introductionmentioning
confidence: 99%